2013
DOI: 10.1890/es13-00013.1
|View full text |Cite
|
Sign up to set email alerts
|

Risk taking not foraging behavior predicts dispersal of recently emerged stream brook charr (Salvelinus fontinalis)

Abstract: Abstract. Several hypotheses predict that individual differences in migration and dispersal are related to individual differences in routine behavior associated with foraging and risk taking. We tested whether short-term dispersal of recently emerged brook charr Salvelinus fontinalis was correlated with differences in activity during prey search in the field (a measure of foraging tactic) or in the time taken to exit a dark tube into an unfamiliar field environment (a measure of risk taking). For one sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
4
1
Order By: Relevance
“…We found no evidence for a dispersal syndrome, with the lack of correlation between dispersal from release and other behavioral traits at the between-individual level, indicating that individuals that dispersed further from the release site did not have consistently larger HRs, higher vertical activity and movement rates, or reduced site fidelity on a long-term basis. Although our data are not directly comparable to other authors who found dispersal correlated with other behavioral traits (Fraser et al 2001;Edelsparre et al 2013), our data suggest that simple linear dispersal from release measures, which are quite frequently used to interpret the spatial ecology of fishes, may be too simple to capture much of the within-population diversity in spatial behaviors. Our detection of significant phenotypic correlations (Table 4) between dispersal and movement, dispersal and HR, and dispersal and site fidelity reduction might historically have been interpreted as evidence of behavioral syndrome.…”
Section: Discussioncontrasting
confidence: 99%
“…We found no evidence for a dispersal syndrome, with the lack of correlation between dispersal from release and other behavioral traits at the between-individual level, indicating that individuals that dispersed further from the release site did not have consistently larger HRs, higher vertical activity and movement rates, or reduced site fidelity on a long-term basis. Although our data are not directly comparable to other authors who found dispersal correlated with other behavioral traits (Fraser et al 2001;Edelsparre et al 2013), our data suggest that simple linear dispersal from release measures, which are quite frequently used to interpret the spatial ecology of fishes, may be too simple to capture much of the within-population diversity in spatial behaviors. Our detection of significant phenotypic correlations (Table 4) between dispersal and movement, dispersal and HR, and dispersal and site fidelity reduction might historically have been interpreted as evidence of behavioral syndrome.…”
Section: Discussioncontrasting
confidence: 99%
“…The shape‐dependent use of Copepoda, and subsequent parasite exposure, appears not to result from biomechanical limitations involving prey capture: Thingvallavatn planktivore charr frequently consume Daphnia which are less parasitized and more easily captured than Copepoda (Malmquist, ; Malmquist et al ., ; Franklin, ). Alternative explanations for shape‐dependent resource use may involve hydrodynamic demands associated with behaviours such as increased search behaviours, and/or boldness in foraging farther from the shoal (Ehlinger, ; Mikheev et al ., ; Adams, ; Edelsparre et al ., ). Shape‐dependent parasitism was also evident in small benthic and brown charr, but without subsequent effects on growth.…”
Section: Discussionmentioning
confidence: 97%
“…Several researchers have proposed that variation in dispersal patterns may be driven by intrinsic differences in the behaviour of individuals (i.e. personalities, R eale et al 2007;Cote et al 2010) such as sociability (R eale et al 2007;Seyfarth et al 2012), shy-bold (Fraser et al 2001;Edelsparre et al 2013), and foraging phenotypes (Grinnell 1931;O'Riain et al 1996;Meylan et al 2009). Over 80 years ago Grinnell (1931) proposed that large-scale animal movements could arise from variation in routine behaviours such as foraging.…”
Section: Introductionmentioning
confidence: 99%